Efesus 1:13 dalam Terang Teologi Kovenan: Roh Kudus sebagai Materai Janji Allah - Purwonugroho, Daniel Pesah (Sekolah Tinggi Teologi Parakletos Tomohon, 2025)
Abstract: This paper aims to expose Ephesians 1:13 regarding the Holy Spirit as the seal of God's promise through the light of covenant theology. The sealing of the Holy Spirit is a metaphor that has deep theological and spiritual meaning. The sealing of the Holy Spirit signifies God's ownership of His people. It enables God's people to receive the divine inheritance. The sealing also guarantees a covenant between God and His people, where the sealing of the Holy Spirit is a guarantee of the divine inheritance that God promises. Through a descriptive qualitative approach, the author tries to unravel Ephesians 1:13 in the light of covenant theology regarding the sealing of the Holy Spirit in God's promise. The author states that the sealing of the Holy Spirit in Ephesians 1:13 can be understood through the perspective of covenant theology. This understanding has a significant impact on the lives of believers. This paper provides a theological contribution that states Ephesians 1:13 in a covenantal perspective and highlights the role of the Holy Spirit in the dynamics of God's covenant. Abstrak: Tulisan ini bertujuan untuk mengekspos Efesus 1:13 mengenai Roh Kudus sebagai meterai janji Allah melalui terang teologi kovenan. Pemeteraian Roh Kudus merupakan metafora yang memiliki makna teologis dan spiritual yang mendalam. Pemeteraian Roh Kudus menandakan kepemilikan Allah dengan umatNya. Hal tersebut membawa umat Allah dapat menerima warisan ilahi. Pemeteraian tersebut juga menjamin sebuah kovenan antara Allah dengan umatNya dimana meteriao Roh Kudus merupakan jaminan atas warisan ilahi yang Allah janjikan. Melalui pendekatan kualitatif deskriptif, penulis mencoba mengurai Efesus 1:13 melalui terang teologi kovenan mengenai pemeteraian Roh Kudus dalam janji Allah. Penulis menyatakan bahwa pemeteraian Roh Kudus dalam Efesus 1:13 dapat dipahami melalui perspektif teologi kovenan. Pemahaman tersebut berdampak signifikan bagi kehidupan orang percaya. Tulisan ini memberikan sebuah sumbangsih teologis yang menyatakan Efesus 1:13 dalam pespektif kovenantal dan menyoroti peran Roh Kudus dalam dinamika Kovenan Allah.